Temperature and pressure variations in salt compressed air energy storage (CAES) caverns considering the air flow in the underground wellbore. (1st August 2022) - Han, Yue; Cui, Hao; Ma, Hongling; Chen, Jianlin; Liu, Ning
Abstract: The flow of compressed air in the wellbore affects the thermodynamic performance in the salt compressed air energy storage (CAES) cavern and this effect is still uncharted. In this study, a coupled explicit finite difference model considering the wellbore flow is proposed to obtain thermodynamic performance of the compressed air in the cavern. It is found that the thermodynamic performance is directly determined by the air temperature and pressure at the wellbore outlet, which are changed by the flow in the wellbore. A sensitivity study shows that the injection mass rate is the key parameter and significantly increases the air temperature and pressure in the cavern. The injection temperature and wellbore length are secondary factors. A high injection pressure is beneficial for energy storage. The inner diameter, roughness and thermal conductivity of the wellbore influence the performance slightly. The developed combined model is a more accurate tool for predicting the thermodynamic performance of a deep CAES cavern. Highlights: A thermodynamic model considering the wellbore flowis proposed. Air temperature and pressure variations in the wellbore and cavern are studied. The injection mass rate is the critical factor that significantly influence the thermodynamic performance.